The relationship between lower limb muscle strength and lower extremity function in HIV disease - Peter C. Mhariwa; Hellen Myezwa; Mary L. Galantino; Douglas Maleka (AOSIS, 2017)
Background: Human immunodeficiency virus (HIV) negatively impacts muscle strength and function. This study aimed to establish the relationship between lower limb muscle strength and lower extremity function in HIV disease. Method: A cross-sectional study was undertaken with a sample of 113 HIV-positive participants. Lower limb muscle strength and self-reported function were established using dynamometry and the Lower Extremity Functional Scale (LEFS), respectively. Muscle strength and functional status were established in a subset of 30 HIV-negative participants to determine normative values. Results: Muscle strength for participants with HIV ranged from an ankle dorsiflexion mean of 9.33 kg/m2 to 15.79 kg/m2 in hip extensors. In the HIV-negative group, ankle dorsiflexors recorded 11.17 kg/m2, whereas hip extensors were the strongest, generating 17.68 kg/m2. In the HIV-positive group, linear regression showed a positive relationship between lower limb muscle strength and lower extremity function (r = 0.71, p = 0.00). Fifty per cent of the changes in lower extremity function were attributable to lower limb muscle strength. A simple linear regression model showed that lower limb ankle plantar flexors contributed the most to lower extremity function in this cohort, contrary to the literature which states that hip and trunk muscles are the most active in lower limb functional activities. Conclusion: Lower extremity strength impacts perceived function in individuals stabilised on antiretroviral therapy for HIV disease. These findings demonstrate that ankle plantar flexors produce more force over hip flexors. Careful attention should be paid to the implications for strength training in this population.